VDR LOWERS THE RISK OF INFECTION TO IMPROVE THE QUALITY OF NURSING SERVICES: A SYSTEMATIC REVIEW - Andi Mappanganro1,2, Ariyanti Saleh3*, Mochammad Hatta4, Kusrini S Kadar5, Nursalam6, Agussalim Bukhari7, Saldy Yusuf8, Kidri Alwi9, Aulia Insani Latif10, Abdul Thalib11 (Chelonian Research Foundation, 2023)
Background: The high prevalence of infection reaches 7.1% in European countries, 4.5% in the US, and ranges from 3.5% to 12% in other developed countries. The discovery of VDR has become one of the solutions in reducing the risk of infection, where VDR acts as a transcription factor by modulating gene expression that triggers the immune response to the infection. Objectives: This study aims to systematically evaluate and describe the role of VDR in reducing the risk of infection to improve the quality of nursing services. Methods: A systematic literature search was conducted on 5 databases, namely Google Scholar, PubMed, ProQuest, Sage, and ScienceDirect for articles published in the last 5 years in English, related to the role of VDR in reducing infections in nursing. Results: Based on the analysis of 10 articles, VDR plays a role in inhibiting cancer cell proliferation, killing bacteria in typhoid fever, playing a protective role against bacterial challenges, regulating intestinal homeostasis by preventing the invasion of pathogenic bacteria, acting as a potent immunomodulator and antimicrobial agent, mediating protection against infections by supporting antiviral responses, acting as an anti-inflammatory, antiproliferative, and antitumorigenic agent, and alleviating intestinal fibrosis by inhibiting EMT (Epithelial-Mesenchymal Transition). Conclusion: VDR reduces the risk of infection by killing bacteria and viruses, especially in the intestine, controlling gastrointestinal homeostasis, acting as an anti-inflammatory and antiproliferative agent, and playing a prognostic role. Keywords :VDR, Infection, Nursing